The effect of salinity stress towards expression of thiamine biosynthesis genes (THIC and THI1/THI4) in oil palm (Elaies guineensis) - Abdul Rahman, Nur Syuhadah (2015)
Thiamine or also known as vitamin B1, it is the first water soluble B-complex vitamin to be identified which plays an important role as a cofactor and as a non-cofactor as well. As a cofactor, it is important for various types of enzymes involved in central metabolism such as pyruvate decarboxylase, pyruvate dehydrogenase, α-ketoglutarate dehydrogenase and transketolase in its active form, thiamine pyrophosphate (TPP). As a non-cofactor, it has been shown to have a role in plant protection against stress. Salinity stress is one of the most critical abiotic stresses that affects the productivity and growth of a plant. Plus, Malaysia is now the second largest producer and exporters of palm oil but the oil palm plantations recently facing problems due to the plant stresses. Thus, we investigated what happens to the first two enzymes involved in thiamine biosynthesis pathway, THIC and THI1/THI4 when subjected to salinity stress induced by sodium chloride (NaCl) in oil palm. Eight pairs of primer were designed based on consensus sequence of other genes obtained from Oryza sativa, Zea mays, Arabidopsis thaliana and Alnus glutinosa. Total RNA was extracted from spear leaf tissue samples that being treated with 0 mM, 50 mM, 150 mM and 200 mM of sodium chloride solution for 3 days, 7 days and 30 days. Then, RT-PCR was conducted to amplify both gene transcripts. As for THIC, the highest level of expression was observed on day 7 for 50 mM NaCl treated oil palm seedling with an increase of up to 331% level of expression compared to the untreated seedling with 100%. For THI1/THI4 gene transcript, the highest level of expression was 723% on day 3 for 200 mM NaCl treated oil palm seedling when compared to the untreated palm with 100%. The results showed that relatively higher levels were observed in THI1/THI4 for its additional role in protecting DNA from damage compare to TH1C. Sequence verification was conducted to confirm the amplification of THIC and THI1/THI4 gene transcripts. This study supports the finding suggesting that thiamine may play a role in plant protection against stress as it may lead to an overexpression of thiamine in general.